2022
DOI: 10.1038/s41467-022-32915-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C epigenetically controls osteogenesis and bone mineralization

Abstract: Vitamin C deficiency disrupts the integrity of connective tissues including bone. For decades this function has been primarily attributed to Vitamin C as a cofactor for collagen maturation. Here, we demonstrate that Vitamin C epigenetically orchestrates osteogenic differentiation and function by modulating chromatin accessibility and priming transcriptional activity. Vitamin C regulates histone demethylation (H3K9me3 and H3K27me3) and promotes TET-mediated 5hmC DNA hydroxymethylation at promoters, enhancers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 78 publications
(98 reference statements)
1
25
1
Order By: Relevance
“…Intriguingly, recent research indicates that inhibiting prolyl-hydroxylase activity using its specific inhibitor 1,4-DPCA does not stop the expression of the mature osteoblastic gene, suggesting that osteogenic transcriptional program is independent of collagen synthesis during osteoblastogenesis. (38) On the other hand, several studies indicated that the endogenous CaMKII activity plays an important role in cartilage hypertrophy via modulating Col10a1 biosynthesis in hypertrophic chondrocytes. (39)(40)(41) In this study, we demonstrated that MAP promoted Col1a1 biosynthesis in SSPCs by activating the CaMKIIα.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent research indicates that inhibiting prolyl-hydroxylase activity using its specific inhibitor 1,4-DPCA does not stop the expression of the mature osteoblastic gene, suggesting that osteogenic transcriptional program is independent of collagen synthesis during osteoblastogenesis. (38) On the other hand, several studies indicated that the endogenous CaMKII activity plays an important role in cartilage hypertrophy via modulating Col10a1 biosynthesis in hypertrophic chondrocytes. (39)(40)(41) In this study, we demonstrated that MAP promoted Col1a1 biosynthesis in SSPCs by activating the CaMKIIα.…”
Section: Discussionmentioning
confidence: 99%
“…In the Gulo -/- mice model, where mice can only consume Vitamin C through exogenous supplementation, five weeks of Vitamin C deprivation elevated H3K9me3 and H3K27me3 marks in bone tissue. Furthermore, the knockdown of H3K9me3 demethylases KDM4A and KDM4B significantly downregulated the osteogenic capacity of MSCs ( 137 ).…”
Section: Epigenetic Control Of Mscs In Bone Regenerationmentioning
confidence: 99%
“…Intracellular biosynthetic and metabolic systems are very diverse to maintain normal physiological requirements. , Amino acid metabolism, citric acid metabolism, glycolytic metabolism, and urea metabolism cycles provide the basis for the synthesis of organic small molecules and organic polymers. Intracellular or extracellular biomineralization systems provide the chemical basis for the synthesis of inorganic nanomaterials, such as physiological mineralization and pathological mineralization. The multidimensional structure of proteins is the site of nucleation for biomineralization of inorganic nanomaterials, or reduced biomolecules provide the chemical energy for biochemical synthesis and ultimately the formation of nanomaterials with specific functions. , This hints that the biosynthesis system may be an outstanding reactor to synthesize nanoprobes that can be used for chemical biomedical imaging.…”
Section: Biosynthesis Systemsmentioning
confidence: 99%